Teachers' perceptions on reflective practices in higher education institutions: A case study - Wahba, Samar (AUC Knowledge Fountain, 2019)
This study examines the perceptions of teachers on their reflective practices in private higher education institutions.The aim of the study is to understand how teachers' perceptions on their practices may impact the development of their teaching methods. The research investigates the views of teachers on their reflective practices and examines the teachers' approaches in applying such practices in teaching to establish whether these reflective practices are important and to what extent they benefit the teacher. This research focuses on English departments within the context of private institutions: The American University in Cairo (AUC) and Misr International University (MIU). A qualitative approach was utilized in this study.Ten faculty members voluntarily participated in a one-on-one interview.The study adopts the experiential learning cycle as its theoretical framework focusing on the stages of reflection.The results appear to support the finding that instructors of both AUC and MIU were aware of the significance of reflection because it has positive impact on their teaching. Moreover, self-reflection on practices appeared to be plausible and experienced by individual participants as helpful. Furthermore, they were valuing feedback from students and peers to a great extent. Furthermore, teachers were both self-reflecting to ensure they were doing their jobs properly and meeting students' needs.There was an indication that they wanted to improve in their own performance in order to enhance and enrich students'learning. Data collected and literature in this research have demonstrated that reflective practices should be reinforced and incorporated in teaching because it has positive impact on teacher instruction. Opportunities for future research may involve analysis of the means that can enhance teachers' reflective practicesand the way reflective practitioners can be cultivated.